Document transmitted to the General Assembly of the State of Connecticut, accompanying the governor's message, May session, 1821 (LLMC-digital (Series), 1821)
Report by Maryland's Committee to Whom was Referred so much of the Governor's Message, as relates to Education and Public Instruction, as transmitted to the Connecticut General Assembly by Governor Wolcott of Connecticut.